2017
DOI: 10.1155/2017/9081802
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Pain and Sleep Disorders in Primary Care

Abstract: Background Chronic pain (CP) and sleep disorders (SD) are highly prevalent in the general population. However, comprehensive data regarding the prevalence and characteristics of pain and SD in primary care are rare. Methods From N = 578 patients N = 570 were included within 8 weeks (mean age: 50.8 ± 18.7 years, females: 289). Sociodemographic data, Insomnia Severity Index (ISI), and parts of a self-report questionnaire for pain (Multidimensional German Pain Questionnaire) were recorded and additional medical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 85 publications
0
53
0
6
Order By: Relevance
“…Hence, insomnia prevalence's ranging from 5 to 50% reported in those works have to be interpreted with caution (18)(19)(20)(21)(22)(23)(24)(25). An exception was the report by Jank et al who employed the ISI for analyzing insomnia in a mixed group with and without pain complaints (40). In this sample of 570 patients from Austria, insomnia prevalence was 29.1%, with 55 subjects (9.6%) complaining of clinically relevant insomnia.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Hence, insomnia prevalence's ranging from 5 to 50% reported in those works have to be interpreted with caution (18)(19)(20)(21)(22)(23)(24)(25). An exception was the report by Jank et al who employed the ISI for analyzing insomnia in a mixed group with and without pain complaints (40). In this sample of 570 patients from Austria, insomnia prevalence was 29.1%, with 55 subjects (9.6%) complaining of clinically relevant insomnia.…”
Section: Discussionmentioning
confidence: 81%
“…Hence, the results do not allow inferring potential time-related dynamics. As only few studies report high quality prevalence data of insomnia in persons suffering from pain (40,41), the inclusion of age and gender paired controls would be an interesting aspect to be considered in future studies. As we aimed at reporting insomnia in a representative sample of our clinic population, we also included persons aged 10-20 years, even though the ISI is not specifically validated for this age group.…”
Section: -mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, chronic pain, which is common among healthcare workers,24 has been shown to be related to sleep problems,25 although it remains unclear which specific site of chronic pain most greatly affects sleep problems. Health-related behaviours are also an important potential influencing factor.…”
Section: Introductionmentioning
confidence: 99%
“…More patients were experiencing sleep disorders in chronic pain group than the others; but this result was not statistically significant. One may expect a relation between pain and sleep disturbance; as Jank et al (44) found that 45.5% of the patients suffering from chronic pain were experiencing sleep disorders and chronic pain and older age were significantly associated with sleep problems. In fact, the assessment of sleep disturbance is completely subjective and prone to inacurate recall and memory bias; therefore, studies with more objective diagnostic measures (like polysomnography) are needed.…”
Section: Discussionmentioning
confidence: 99%